WINNING STRATEGY MUHAMMAD LUTFI- FERRY SOFIYAN IN ELECTION CONCURRENT 2018 IN THE CITY OF BIMA - WAHYU UDIN; SUNARSO SUNARSO (Universitas Muhammadiyah Yogyakarta, 2020)
Local elections in 2018 will be followed by 171 regions spread across 34 provinces throughout Indonesia. The 2018 simultaneous local elections aim to elect regional leaders, namely the Governor and the Major / Regent. The City of Bima is a part of the simultaneous local election to elect the Major and Deputy Major of Bima. The election contest was followed by the couple Muhammad Lutfi and Feri Sofiyan from the Golkar and PAN parties. This couple is known by their supporters as Lutfer (Lutfi Feri). The couple's victory is inseparable from the strategy used to win the position of Major and Deputy Major of Bima 2018. Therefore, in this paper discuss the strategy used by the Lutfer pair in winning political competition in the City of Bima. The winning strategy includes the strategy carried out by the candidate pair, the coalition / bearer party, the success team and volunteers / sympathizers. The method used in this paper is based on the results of research by researchers in the City of Bima. The purpose of this paper is to find out the strategies used by the Lutfer pair, coalition / bearer parties, success teams, and volunteers / sympathizers in winning the 2018 Bima Major election. The results of the study show the strategies adopted by the candidate pairs, coalition / bearer parties, team success, volunteers / sympathizers include network strategies (actors, establishing communication), imaging strategies (print media / electronic media messages) and political campaign strategies ( political attributes, meetings).